PROTEIN RESIDUE (CIEP) ANALYSIS FOR SAMPLES FROM SITE (HIOV-155), WOOD BUFFALO REGIONAL MUNICIPALITY, ALBERTA, CANADA - Cummings, Linda Scott (2020)
Site HiOv-155 is located north of Fort McMurray in northeastern Alberta, Canada. Three flaked lithics, including one complete Agate Basin projectile point and two biface fragments, recovered during excavation were submitted for protein residue analysis to identify animals that either were killed or processed.